2022
DOI: 10.1037/pst0000389
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-focused therapy for fear of cancer recurrence: A hospital-based exploratory outcome study.

Abstract: Fear of cancer recurrence (FCR) is a main concern for most cancer survivors and can bring significant distress impacting well-being and quality of life. Although other psychological approaches have been developed for dysfunctional FCR, based on previous research, emotion-focused therapy (EFT) might also be a relevant intervention for treating this concern. A total of 17 adults with a cancer diagnosis and presenting FCR among other cancer-related concerns were offered EFT, delivered in a regular practice in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
(69 reference statements)
0
10
0
1
Order By: Relevance
“…This highlights a critical need for future studies to examine the efficacy and effectiveness of other psychotherapy theories when working with populations navigating physical health issues or employed in the health care setting. For example, in this special section, Almeida et al (2022) demonstrated that emotion-focused therapy was perceived as helpful and showed significant effects on psychotherapy outcomes (albeit not clinically reliable change) among people experiencing fear of cancer reoccurrence. As noted in the introduction to the special section (Raque & Mitchell, 2022), theories that more fully address power, oppression, and privilege, like relational-cultural theory (Miller, 1976) and narrative therapy (White & Epston, 1990), have received very limited attention by psychotherapy health researchers.…”
Section: Personalmentioning
confidence: 94%
See 2 more Smart Citations
“…This highlights a critical need for future studies to examine the efficacy and effectiveness of other psychotherapy theories when working with populations navigating physical health issues or employed in the health care setting. For example, in this special section, Almeida et al (2022) demonstrated that emotion-focused therapy was perceived as helpful and showed significant effects on psychotherapy outcomes (albeit not clinically reliable change) among people experiencing fear of cancer reoccurrence. As noted in the introduction to the special section (Raque & Mitchell, 2022), theories that more fully address power, oppression, and privilege, like relational-cultural theory (Miller, 1976) and narrative therapy (White & Epston, 1990), have received very limited attention by psychotherapy health researchers.…”
Section: Personalmentioning
confidence: 94%
“…Research examining the benefits of psychotherapy among populations navigating physical health conditions or employed in the health care setting is needed. As described and replicated in articles within this special section (Almeida et al, 2022;Kilkus, 2022;King et al, 2021;Richey & Pointer, 2021;Piers et al, 2021), much of the literature in this area has focused on cognitive behavioral therapy. This highlights a critical need for future studies to examine the efficacy and effectiveness of other psychotherapy theories when working with populations navigating physical health issues or employed in the health care setting.…”
Section: Personalmentioning
confidence: 96%
See 1 more Smart Citation
“…The next two articles in the second part focus specifically on cancer survivorship, the first of which presents a theoretical overview of how to apply CBT (Kilkus, 2022) and the second provides preliminary data on an emotion-focused therapy (EFT) intervention to address survivors’ fear of cancer recurrence (Almeida et al, 2022). Given the prevalence of cancer in the United States, one in two men and one in three women will develop cancer at some point during their lifetime (American Cancer Society, 2016); psychotherapists may find these two articles helpful for addressing survivors’ personal sites of well-being.…”
Section: This Special Sectionmentioning
confidence: 99%
“…Kondisi perubahan yang paling tampak adalah Claudia tidak lagi mengembangkan emotional blocking. Sejumlah penelitian aplikasi EFT pada individu lansia dengan permasalahan kesehatan spesifik, seperti kanker dan kanker payudara dengan komorbid gangguan depresi, menunjukkan bahwa EFT dapat menurunkan gejala depresi pada partisipan (Connolly-zubbot et al, 2019;Almeida et al, 2022;Hissa et al, 2022;Salarirad et al, 2022).…”
unclassified